2016
DOI: 10.1002/jrs.4955
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of nitromethane mixed with IR780 dye studied by coherent anti-stokes Raman spectroscopy

Abstract: Vibrational coupling between different kinds of molecules in liquid mixture is studied by multiplex coherent anti‐Stokes Raman spectroscopy (CARS). To identify vibrational coherence, fs‐probe with high time resolution and narrowband‐probe with high spectral resolution are adopted in CARS experiments. Using liquid nitromethane (NM) mixed with organic dye IR780 perchlorate as the sample, we can clearly observe the interference between different vibrational modes. The intermolecular vibrational interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…The main strength of the Raman spectroscopy is able to provide a great wealth of molecular vibration information. [ 40,41 ] The experimental Raman spectra of benzofuroxan at the selected pressure in the spectral range of 400–1,700 cm −1 have been shown in Figure 2. It can be seen that there are about 15 Raman bands ( v 1 –v 15 ) that can be observed at ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The main strength of the Raman spectroscopy is able to provide a great wealth of molecular vibration information. [ 40,41 ] The experimental Raman spectra of benzofuroxan at the selected pressure in the spectral range of 400–1,700 cm −1 have been shown in Figure 2. It can be seen that there are about 15 Raman bands ( v 1 –v 15 ) that can be observed at ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The vibrational modes and the corresponding Raman shifts of the MG molecules and the IR780 molecules are also listed in Table S1 in the Supporting Information. [46][47][48][49][50] The SERS signals for the R6G, MG, and IR780 molecules excited at other wavelengths are very weak or cannot be detected at all. This result strongly suggests that the molecular resonance combined with the photons may play the most important role in the SERS mechanism of the TaSe 2 film and the photon-induced charge transfer (PICT) is verified in the following discussion.…”
Section: Sers Performances Of Tasementioning
confidence: 99%
“…In our previous work, we observed similar cases in IR780/NM solution and demonstrated that the bad spectral resolution did not influence the analysis of vibrational coupling. 23 For Raman mode assignment, the Raman spectrum of α-RDX was calculated by ab initio calculations using the B3LYP density functional theory method with the Sadlej's mediumsized polarized basis set (SadlejpVTZ). Calculations were performed with the Gaussian 03 computation package.…”
Section: Time-and Frequency-resolved Cars Spectrummentioning
confidence: 99%